Student performance and ventilation mechanism in local elementary school - Teo, Yong Da. (2012)
This research report provides a state-of-the-art investigation on the indoor air quality in Singapore’s primary schools. Indoor air quality is recognized as a significant health, environment and economic problem. Poor indoor air quality is linked to health illness such as the ‘Sick Building Syndrome’ (SBS), which affects the health and well-being of a student. As for children, they spend most of their time in schools thus the indoor air quality plays a vital role in determining the students’ health, well-being and performance.This study explores the association between the students’ health, well-being and performance